MAKNA FILOSOFI DAUN SAMBABELUM DALAM UPACARA PERKAWINAN AGAMA HINDU KAHARINGAN DI DESA PENDA NANGE KECAMATAN BUKIT RAYA KABUPATEN KATINGAN - Rumina, Rumina; Arta, I Gede Arya Juni (Widya Katambung, 2025)
Sambabelum leaves are one of the plants that are easily found around the environment and are also found in Hindu Kaharingan wedding ceremonies. Hindu Kaharingan people generally only know their use as equipment in wedding ceremonies and consider them as ordinary plants. Based on this, this study focuses on the philosophical meaning of sambabelum leaves in Hindu Kaharingan wedding ceremonies. This study uses a qualitative method, with a field study type of research. Qualitative data is used as the main data, while quantitative data is only as additional data. Determination of informants using purposive sampling techniques. Based on the research results, it is known that sambabelum leaves (kalanchoe pinneta) have a deep philosophical meaning in the Hindu Kaharingan wedding ceremony, as follows: a). The meaning of fertility, namely sambabelum leaves symbolize the hope for healthy offspring, a prosperous family, and an abundant life. b). The meaning of purity and purification, where sambabelum leaves are used in the purification process, cleansing negative energy and bringing purity to the couple who are going to get married. c). The meaning of blessing and prosperity, namely sambabelum leaves become prayers and requests to spiritual powers to provide blessings, protection, and prosperity in married life. d). The meaning of balance, where sambabelum leaves symbolize balance and harmony between the bride and groom, as well as a balanced relationship between humans and nature. e). The meaning of togetherness, namely sambabelum leaves describe a commitment to support each other, complement each other, and share life together in joy and sorrow. f). The meaning of harmony and happiness, namely the sambabelum leaf is a symbol of hope for a married life full of happiness and success for married couples. g). The meaning of religion and tradition, namely the sambabelum leaf is part of the tradition and cultural heritage of the Hindu Kaharingan religion, strengthening the cultural identity of the local community and preserving important traditional values